Exploring the relationship between resilience, sense of coherence, and social support in a sample of nurses during the spread of COVID-19: a mediation analysis study - Rohani, Camelia; Ahmadi, Mehrnaz; Seyedtabib, Maryam; Mehdipoorkorani, Ladan (Frontiers in Public Health, 2025)
BackgroundDuring the spread of COVID-19, nurses on the front line of fighting the disease experienced severe psychological pressures. The ability to adapt to difficult situations is an essential requirement for maintaining individuals’ endurance during a crisis. This study was designed to explore the relationship between three outcome variables of resilience, sense of coherence (SOC), and perceived social support in a sample of Iranian nurses during the spread of the COVID-19 pandemic.MethodsA cross-sectional study with a correlational design was conducted on 360 registered nurses from six university hospitals during the seventh wave of COVID-19 in our society. Data collection was conducted by the demographic information questionnaire, the Connor–Davidson Resilience Scale (CD-RISC), the Sense of Coherence Scale (SOC-13), and the Multidimensional Scale of Perceived Social Support (MSPSS).ResultsThe results of the structural equation modeling (SEM) showed that social support had a direct positive effect on the SOC (β = 0.498, p < 0.001), and the SOC had a direct positive effect on the resilience (β = 0.688, p < 0.001). Furthermore, we found an indirect effect of social support on resilience through the complete mediating role of the SOC.ConclusionThe full mediating role of SOC in the relationship between social support and resilience showed that nurses with a higher level of SOC had a better understanding of social support, and this can influence their resilience in the COVID-19 crisis. This is theoretical support for the application of the salutogenic approach to health intervention plans to promote a healthy orientation in nurses toward mobilizing resources.